Status of coconut basal stem rot disease in India – A review - SNEHALATHARANI, A; MAHESWARAPPA, H P; DEVAPPA, V; MALHOTRA, S K (The Indian Journal of Agricultural Sciences, 2016)
Basal stem rot is one of the important diseases of coconut accounting to severe yield loss in southern India. The disease in Indian subcontinent is reported to be caused by G. lucidum (Leys.) Karst., G. applanatum (Pers.) Pat. And G. boninense. Present status of the disease pertaining to occurrence and distribution in major coconut growing states, symptomology, etiology and epidemiology, disease indexing, pathogen diversity and its management methods are reviewed. The disease if unattended, is becoming a major threat to coconut production in Andhra Pradesh, Karnataka and Tamil Nadu states. Management of the disease is possible with continuous monitoring and implementing biocontrol based integrated management even though there is variation among the pathogenic virulence of Ganoderma isolates. As early disease escapes detection, recent developments in early detection, grouping and molecular identification of the pathogen and integrated disease management measures are summarized in this review paper.